A study the effect of the broodstock density on reprodustive and culture of hirudinea manillensis (green leech) - Azree Izwan Salleh (2013)
Hirudinae Maniliens is also called as 'Buffalo leech' or Lintah Kerbau are distributed in several countries in Southeast Asia such as Southern China, Philippines, Thailand, Vietnam and Malaysia (Department of Fisheries Malaysia, 2009). In this study, effect of densities in culturing and reproduction of Hirudinae manillensis or buffalo leech were observed and it is recorded. Determining optimum density for culturing leeches is one of the main factors for successful culture and reproduction. The investigation has demonstrated that broodstock density significantly affects the reproductive efficiency of the leech H. manillensis. A broodstock density of 15-20 parent leeches per tank (0.10 m3 soil per tank) is recommended for the commercial culture of this leech species. Fresh eel's blood was recommended for the commercial breeding of this species. The choice of diet for these leeches is important for the growth and survival of the juveniles whereby given the fresh eel's blood shows the positive effect on both condition and highly recommended as the diet for the first two months after cocoon deposition. The average number of cocoons was highest in 20 individual broodstock's tank with mean and standard deviation of 5.667±0.577 followed by 15 individual broodstock's tank with mean 2.667±1.528. The condition under 20 individual broodstock's tank had the highest hatching number with mean and standard deviation of 2.027±0.914 while the lowest number of hatching under 15 individual broodstock's tank with mean and standard deviation of 1.220±1.577. In 20 individual broodstock's tank had the highest hatching rate with a value of mean and standard deviation of 1.640±2.055 but this was not significant different among all other condition tested. The highest mortality rate was 20 individual broodstock's tank with a value of mean and standard deviation of 8.000±3.606 compared with the lowest mortality rate in 5 individual broodstock's tank with a value of mean and standard deviation of 1.667±0.577. All densities give significant difference.